Causes of Personal Financial Stress in Malaysia: A Phenomenological Study - ADNAN, AHMAD AZRIN; ZIN, SAKINAH MAT; AZIZ, MOHAMAD IZZUDDIN ABDUL; ESA, JUNAINAH AHMAD; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
Weak financial planning is often the root cause of individual financial stress in Malaysia. However, this phenomenological study has discovered another major rationale. This paper attempts to explain the causes of financial stress among individuals who are almost bankrupt in Malaysia through a phenomenological approach. Three participants were involved in the observation and in- depth interviews. The classification of phenomenological data in the form of specific themes is analysed through continuous comparison methods. This study found that inaccurate tasawur or consumerism pattern had greater influence on individual financial stress than poor financial planning. The inaccurate consumerism tasawur has generated a mystical element of financial stress which is rarely discussed. These findings established the need to re-evaluate the aspects of sustainable lifestyle culture in Malaysia, and it is worth investigating.